CYPERACEAE OF THAILAND II - Kern, J. H. (REINWARDTIA, 1962)
This supplement contains an account of a rather large number of Thailand specimens, collected by A. F. G. Kerr, Marcan, Put, and some others, kindly sent on loan to me by the Keeper of the British Museum (Nat. Hist.), Botany Department, Mr J. E. Dandy. A few additions from the Rijksherbaiium, Leyden, marked (L) and Copenhagen, marked (C), & c. are also added. Three species (nos 175 - 177) are new for Thailand. Among them Lipocarplia pygmaea is very remarkable, as it was so far only known from a recent collection by Van Steenis in Cambodia. Probably this dwarfish sedge was often overlooked. From the species recorded for Thailand as doubtful (Kern, I.e. 79) the record of 1. Cyperus eleusinoides Kunth has appeared to be 95. Cyperus nutans Vahl. Furthermore, the record of 7. Mariscus clarkei Turr. could be reduced to a variety of Cyperus cyperoides (L.) O. K. The numbers of the species are those used in the first paper. An index to collectors numbers is given at the end.